Cobalt (Ⅱ)-intercalated layered double hydroxide as an efficient activator for catalytic oxidation of organic contaminants. Issue 5 (October 2022) - Wang, Rongyao; Chen, Fanli; Gao, Lijuan; Ren, Xiaohua; Guo, Weilin
Abstract: The simultaneous optimization and design of catalysts' structure or components are extremely significant approaches to further enhancing the catalytic activity. Herein, cobalt (Ⅱ)-intercalated Ni-Fe layered double hydroxide (Co-NiFe-LDH) was fabricated via a novel topological transformation process and employed as an efficient activator on peroxymonosulfate (PMS) activation for simulated sewage decontamination. Characterizations with state-of-the-art spectroscopies demonstrated Co (Ⅱ) was successfully embedded in the interlayer of NiFe-LDH after reconstruction. Meanwhile, experiments manifested that the Co-NiFe-LDH possessed an enhanced catalytic performance relative to neither pristine NiFe-LDH nor ternary CoNiFe-LDH. The maximum Orange Ⅱ sewage degradation (30 mg L −1, 99.5 %) could be obtained under the optimal conditions (30 min, 120 mg L -1 Co-NiFe-LDH, and 1 mM PMS) with the first-order up to 0.216 min -1 . Encouragingly, the Co-NiFe-LDH/PMS system exhibited stable performance over a wide pH range and low dissolution. It was also found that the superior performance of Co-NiFe-LDH was attributed to the clusters of Co in the interlayer, which can improve electrochemical characteristics, thereby accelerating interfacial electron transfer. Moreover, on the basis of redox cycles of Ni (Ⅱ)/Ni (Ⅲ) and Fe (Ⅱ)/Fe (Ⅲ), a new redox cycle of Co (Ⅱ)/Co (Ⅲ) was discovered in Co-NiFe-LDH, therefore promoting the utilization efficiency of oxidants. Besides, quenching experiments and electron paramagnetic resonance spectroscopy (EPR) demonstrated that SO4 − and OH acted as the dominant active radicals for Orange Ⅱ degradation. It's also encouraging that the Co-NiFe-LDH/PMS system could efficiently decompose other typical contaminants, and its catalytic activity remained unchanged after five uses. Ultimately, a reasonable catalytic mechanism of the Co-NiFe-LDH/PMS system was proposed by the comprehensive analysis. This work sheds light on the elegantly designed LDH with high performance toward activating PMS in water decontamination. Graphical Abstract: ga1 Highlights: Cobalt (Ⅱ)-intercalated Ni-Fe layered double hydroxide was fabricated via a novel topological transformation process. Co-NiFe-LDH possessed an enhanced catalytic performance relative to neither pristine NiFe-LDH nor ternary CoNiFe-LDH. The clusters of Co in the interlayer elucidated the enhanced catalytic activity. The Co-NiFe-LDH/PMS system exhibited the nature of reusability, stability, and universality. SO4 - and OH which generated via breaking the intramolecular peroxide bond in PMS accounted for the removal of pollutants.